2017
DOI: 10.14191/atmos.2017.27.1.093
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint-Based Observation Impact of Advanced Microwave Sounding Unit-A (AMSU-A) on the Short-Range Forecast in East Asia

Abstract: The effect of Advanced Microwave Sounding Unit-A (AMSU-A) observations on the short-range forecast in East Asia (EA) was investigated for the Northern Hemispheric (NH) summer and winter months, using the Forecast Sensitivity to Observations (FSO) method. For both periods, the contribution of radiosonde (TEMP) to the EA forecast was largest, followed by AIRCRAFT, AMSU-A, Infrared Atmospheric Sounding Interferometer (IASI), and the atmospheric motion vector of Communication, Ocean and Meteorological Satellite (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Numerous studies showed that in situ and remote-sensed observations for surface conditions and the upper atmosphere can provide a better description for both storm-scale processes and large-scale environments, leading to improved precipitation forecasts (Zupanski et al, 2002;Cucurull et al, 2004;Zhang et al, 2006;Fillion et al, 2010;Hartung et al, 2011;Hamill et al, 2013;Salslo and Greybush, 2017;English et al, 2018;Zhang et al, 2019). In South Korea, data assimilation also indicated significant benefits for winter forecasts (Kim et al, 2013;Kim and Kim, 2017;Yang and Kim, 2021). For example, Kim et al (2013) demonstrated the assimilation of the conventional surface and upper air observations, aircraft, and multiple satellite observations located upwind or in the vicinity of the Korean Peninsula into the Korea Meteorological Administration (KMA) Unified Model.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies showed that in situ and remote-sensed observations for surface conditions and the upper atmosphere can provide a better description for both storm-scale processes and large-scale environments, leading to improved precipitation forecasts (Zupanski et al, 2002;Cucurull et al, 2004;Zhang et al, 2006;Fillion et al, 2010;Hartung et al, 2011;Hamill et al, 2013;Salslo and Greybush, 2017;English et al, 2018;Zhang et al, 2019). In South Korea, data assimilation also indicated significant benefits for winter forecasts (Kim et al, 2013;Kim and Kim, 2017;Yang and Kim, 2021). For example, Kim et al (2013) demonstrated the assimilation of the conventional surface and upper air observations, aircraft, and multiple satellite observations located upwind or in the vicinity of the Korean Peninsula into the Korea Meteorological Administration (KMA) Unified Model.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that in situ and remote sensed observations for surface conditions and the upper-atmosphere can provide a better description for both storm-scale processes and large-scale environments leading to improved precipitation forecasts (Zupanski et al, 2002;Cucurull et al, 2004;Zhang et al, 2006;Fillion et al, 2010;Hartung et al, 2011;Hamill et al, 2013;Salslo and Greybush, 2017;English et al, 2018;Zhang et al, 2019). In South Korea, data assimilation also indicated significant benefit for winter 95 forecast (Kim et al, 2013;Kim and Kim, 2017;Yang and Kim, 2021). For example, Kim et al (2013) demonstrated the assimilation of the conventional surface and upper air observations, aircraft, and multiple https://doi.org/10.5194/gmd-2021-161 Preprint.…”
mentioning
confidence: 99%
“…forecast(Kim et al, 2013;Kim and Kim, 2017; Yang and Kim, 2021). For example,Kim et al (2013) demonstrated the assimilation of the conventional surface and upper air observations, aircraft, and multiplehttps://doi.org/10.5194/gmd-2021-161 Preprint.…”
mentioning
confidence: 99%